Anonymity Desirable, Bibliography Not Required: A Journey from Psychiatry to Theology - McCallum, Nema (Theology & sexuality, 2007)
As a teenager in the 1990s, I lived in Scotland. I was ensnared by the psychiatric system at that time, in that place. Contrary to popular rhetoric, I don't consider myself to be one of psychiatry's survivors: I will never quite recover from its effects. This article documents how psychiatry slipped into my life with furtive steps, quickly led me to in-patient wards and permanently tattooed its legacy on my body and mind. It is an experiment in reflective creative writing, combining socio-political and theological analysis; and its tale is true. Now, I am a theologian. My theologizing isn't immune from the shadow permanently projected into each now from my encounter with psychiatry. This story is written out of a conviction that all of our theologies have their separate past lives, integrally tied to the experiences, occluded or otherwise, of any person who attempts to think and speak of God.